Multidimensional Sternal Fixation to Overcome a “Floating” Sternum - William Rothstein; Tyler Spata; Bryan Whitson; Ahmet Kilic (Case Reports in Surgery)
This case report describes the repair of a complete sternal dehiscence of the lower right sternum using sternal wires, manubrial plates, and a Talon closure device for rigid, multidimensional sternal fixation. Sternal dehiscence is a rare but significant cause of morbidity for patients undergoing median sternotomy. The risk factors for this complication are well described and although sternal wires have traditionally been used for primary closure, rigid fixation with sternal plates is a viable alternative to avoid dehiscence in this high-risk cohort.